2021
DOI: 10.2903/j.efsa.2021.6623
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of a feed additive consisting of an essential oil from the fruits of Litsea cubeba (Lour.) Pers. (litsea berry oil) for use in all animal species (FEFANA asbl)

Abstract: Following a request from the European Commission, the EFSA Panel on Additives and Products or Substances used in Animal Feed ( FEEDAP ) was asked to deliver a scientific opinion on the safety and efficacy of an essential oil from the fruits of Litsea cubeba (Lour.) Pers. (litsea berry oil), when used as a sensory additive (flavouring) in feed and water for drinking for all animal species. The FEEDAP Panel concluded that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 40 publications
0
17
0
Order By: Relevance
“…The approach followed by the FEEDAP Panel to assess the safety and the efficacy of camphor white oil from C. camphora is in line with the principles laid down in Regulation (EC) No 429/2008 11 and the relevant guidance documents: Guidance on safety assessment of botanicals and botanical preparations intended for use as ingredients in food supplements (EFSA Scientific Committee, 2009 ); Compendium of botanicals that have been reported to contain toxic, addictive, psychotropic or other substances of concern (EFSA, 2012 ); Guidance for the preparation of dossiers for sensory additives (EFSA FEEDAP Panel, 2012b ); Guidance on studies concerning the safety of use of the additive for users/workers (EFSA FEEDAP Panel, 2012c ); Guidance on the identity, characterisation and conditions of use of feed additives (EFSA FEEDAP Panel, 2017a ); Guidance on the safety of feed additives for the target species (EFSA FEEDAP Panel, 2017b ); Guidance on the assessment of the safety of feed additives for the consumer (EFSA FEEDAP Panel, 2017c ); Guidance on the assessment of the safety of feed additives for the environment (EFSA FEEDAP Panel, 2019 ); Guidance on the assessment of the efficacy of feed additives (EFSA FEEDAP Panel, 2018 ); Guidance document on harmonised methodologies for human health, animal health and ecological risk assessment of combined exposure to multiple chemicals (EFSA Scientific Committee, 2019a ); Statement on the genotoxicity assessment of chemical mixtures (EFSA Scientific Committee, 2019b ); Guidance on the use of the Threshold of Toxicological Concern approach in food safety assessment (EFSA Scientific Committee, 2019c ); General approach to assess the safety for the target species of botanical preparations which contain compounds that are genotoxic and/or carcinogenic. 12…”
Section: Data and Methodologiesmentioning
confidence: 99%
“…The approach followed by the FEEDAP Panel to assess the safety and the efficacy of camphor white oil from C. camphora is in line with the principles laid down in Regulation (EC) No 429/2008 11 and the relevant guidance documents: Guidance on safety assessment of botanicals and botanical preparations intended for use as ingredients in food supplements (EFSA Scientific Committee, 2009 ); Compendium of botanicals that have been reported to contain toxic, addictive, psychotropic or other substances of concern (EFSA, 2012 ); Guidance for the preparation of dossiers for sensory additives (EFSA FEEDAP Panel, 2012b ); Guidance on studies concerning the safety of use of the additive for users/workers (EFSA FEEDAP Panel, 2012c ); Guidance on the identity, characterisation and conditions of use of feed additives (EFSA FEEDAP Panel, 2017a ); Guidance on the safety of feed additives for the target species (EFSA FEEDAP Panel, 2017b ); Guidance on the assessment of the safety of feed additives for the consumer (EFSA FEEDAP Panel, 2017c ); Guidance on the assessment of the safety of feed additives for the environment (EFSA FEEDAP Panel, 2019 ); Guidance on the assessment of the efficacy of feed additives (EFSA FEEDAP Panel, 2018 ); Guidance document on harmonised methodologies for human health, animal health and ecological risk assessment of combined exposure to multiple chemicals (EFSA Scientific Committee, 2019a ); Statement on the genotoxicity assessment of chemical mixtures (EFSA Scientific Committee, 2019b ); Guidance on the use of the Threshold of Toxicological Concern approach in food safety assessment (EFSA Scientific Committee, 2019c ); General approach to assess the safety for the target species of botanical preparations which contain compounds that are genotoxic and/or carcinogenic. 12…”
Section: Data and Methodologiesmentioning
confidence: 99%
“…The data submitted by the applicant showed that the production process of the additive star anise terpenes results in an enrichment of the genotoxic carcinogen estragole from star anise oil. This does not accord with the principles outlined in the general approach to assess the safety for the target species of botanical preparations which contain compounds that are genotoxic and/or carcinogenic when used as feed additives (EFSA FEEDAP Panel, 2021a). Any manufacturing processes of botanical feed additives should avoid selective extraction and enrichment of genotoxic and/or carcinogenic substances and should aim at the reduction of these substances.…”
Section: Assessmentmentioning
confidence: 99%
“…The FEEDAP Panel notes that the margin of exposure (MOE) approach was originally designed to allow an assessment of additives with impurities with genotoxic/carcinogenic activity (EFSA, 2005; EFSA SC, 2012), and was later adapted to the assessment of the safety for the target species of feed additives of botanical origin in which genotoxic and/or carcinogenic substances cannot be fully avoided (EFSA FEEDAP Panel, 2021a). In the present feed additive, terpenes and estragole, a genotoxic carcinogen, are selectively extracted and substantially enriched.…”
Section: Assessmentmentioning
confidence: 99%
“…Pers. [ 91 ], cinnamon tincture from the bark of Cinnamomum verum J. Presl [ 92 ], camphor white oil from Cinnamomum camphora (L.) J. Presl [ 93 ], buchu leaf oil from the leaves of Agathosma betulina (P.J. Bergius) Pillans [ 94 ], ylang ylang oil from the flowers of Cananga odorata (Lam.)…”
Section: Applications In the Human Health And Animal Health Areasmentioning
confidence: 99%